Strategic Role of Tourism in Emerging and Consolidating Sub Sahara Africa (Ssa) Destinations - Chijioke NWACHUKWU; Hieu Minh VU (Communications of International Proceedings, 2020)
Recently, the African tourism sector is experiencing steady growth. Nevertheless, a lot needs to be done in terms of harnessing tourism potentials in Africa. The study focuses on the contribution of tourism to Gross Domestic Products (GDP), employment, investment, and visitor exports in nine African countries; namely Botswana, Cape Verde, Ghana, Kenya, Mauritius, Namibia, Seychelles, South Africa, and Tanzania. The authors did trend analyses of the economic contribution of tourism in nine African countries. Secondary data covering 2008-2018 collected from the World Travel and Tourism Council database was used to shed light on the economic contribution of tourism in Africa. We observed that all the economic indicators (GDP, employment, visitor exports, and investment) show a positive and upward trend. South Africa, Kenya, and Tanzania are the top performers among the sampled countries. The study identified challenges and proposed some recommendations to managers and policymakers in the tourism sectors in Africa.
Keywords: GDP; Visitor Exports; Employment; African Countries; Investment.